Concurrence of High Fat Diet and APOE Gene Induces Allele Specific Metabolic and Mental Stress Changes in a Mouse Model of Alzheimer’s Disease - Segev, Yifat; Livne, Adva; Mints, Meshi; Rosenblum, Kobi (Frontiers in Behavioral Neuroscience, 2016)
Aging is the main risk factor for neurodegenerative diseases, including Alzheimer’s disease (AD). However, evidence indicates that the pathological process begins long before actual cognitive or pathological symptoms are apparent. The long asymptomatic phase and complex integration between genetic, environmental, and metabolic factors make it one of the most challenging diseases to understand and cure. In the present study, we asked whether an environmental factor such as high-fat diet would synergize with a genetic factor to affect the metabolic and cognitive state in the ApoE4 mouse model of AD. Our data suggest that a high-fat diet induces diabetes mellitus-like metabolism in ApoE4 mice, as well as changes in BACE1 protein levels between the two ApoE strains. Furthermore, high-fat diet induces anxiety in this AD mouse model. Our results suggest that young ApoE4 carriers are prone to psychological stress and metabolic abnormalities related to AD, which can easily be triggered via high-fat nutrition.